A Kampfschwert from the 15th century – a reinterpretation of the so called 'Teutonic estoc' from the Princes Czartoryski Collection in Cracow, Poland - Talaga Maciej (Acta Periodica Duellatorum)
The paper aims at reinterpreting the so called ‘Teutonic estoc’ (inventory number: MNK XIV-49) from the Czartoryski Princes Collection, Cracow, Poland. Due to the weapon’s unusual construction it has been necessary to draw up precise documentation - written, drawn and photographic. It has been supplemented with research in historical sources and scholarly literature on the subject.